Fear of Victimization among LGBQ, Non-Binary, and Transgender College and University Students in the United States. Issue 1 (2nd January 2023) - Rogers, Sarah A.; Isom, Deena A.; Rader, Nicole E.
ABSTRACT: This study examines fear of victimization (FOV) among lesbian, gay, bisexual, queer (LGBQ), and (T)ransgender college and university students across the US. We expand the FOV literature by examining the relationship between fear and both gender and sexual identities across racial and ethnic lines among college and university students in the US. We find that being a transgender or non-binary (NB) student is significantly associated with FOV, as well as being an LGBQ student. In addition, Black trans/NB students and Black LGBQ non-trans students are both roughly 11 times more likely than their counterparts to report FOV. Being trans/NB matters; it is an independent identity from one's sexuality, and it operates differently across race and ethnicity.